Khazaria in the Ninth and Tenth Centuries - Živkov, Boris (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2015)
In Khazaria in the Ninth and the Tenth Centuries Boris Zhivkov offers a new view on Khazaria by scrutinizing the different visions offered by recent scholarship. The paucity of written sources has made it necessary to turn to additional information about the steppe states in this period, and to analyze exceptional cases not directly related to the Khazars. In re-examining the Khazars, he thus uses not only the known documentary sources and archaeological finds but also what we know from history of religions (comparative mythology), history of art, structural anthropology and folklore studies. In this way the book draws together a synthesis of conclusions, information and theory.